Enhancing the Life Cycle Management of Built Environment With Integrated Land Administration Functions Based on BIM/IFC and LADM - Korkmaz, Oezlem; Yilmaz, Okan; Basaraner, Melih; Alkan, Mehmet (WILEY, 2025)
The maintenance of physical and legal data related to development in different formats necessitates the manual verification of construction projects' compliance with legal requirements and regulations. However, supporting the BIM/IFC standard, which models the design and construction process of buildings, with legal models has the potential to facilitate compliance with legal requirements and regulations, provide clarity in ownership and boundary management, oversee project approval and control, and ensure that legal areas are secured in 3D. This study focuses on the design of an integrated legal model based on the land administration domain model (LADM) standard, considering the functions of land administration in T & uuml;rkiye, and explores the possibilities of mapping this model to the IFC data format. The study aims to represent land administration functions in BIM/IFC projects and integrate these processes with physical development. The findings from testing the proposed framework's applicability on an existing BIM project reveal opportunities for the integrated management of legal processes that create rights, restrictions, and responsibilities (RRRs) in spatial entities with physical processes.
Keywords: 3D RRRs; BIM/IFC; built environment life cycle management; LADM Edition II; partnerships for the goals; MODEL; Geography